2006
DOI: 10.1021/bi060782u
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the DPS-Like Protein from Sulfolobus solfataricus Reveals a Bacterioferritin-Like Dimetal Binding Site within a DPS-Like Dodecameric Assembly,

Abstract: The superfamily of ferritin-like proteins has recently expanded to include a phylogenetically distinct class of proteins termed DPS-like (DPSL) proteins. Despite their distinct genetic signatures, members of this subclass share considerable similarity to previously recognized DPS proteins. Like DPS, these proteins are expressed in response to oxidative stress, form dodecameric cage-like particles, preferentially utilize H 2 O 2 in the controlled oxidation of Fe 2+ , and possess a short N-terminal extension imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
60
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 61 publications
(106 reference statements)
4
60
0
Order By: Relevance
“…Archaeal DPSL proteins are further distinguished by a pair of conserved cysteine residues, apparently unique to the DPSL proteins, that are juxtaposed to the bacterioferritin-like dimetal binding site. This cysteine pair and the bacterioferritin-like ferrioxidase center, all housed within a dodecameric oligomer, are hallmarks of the archaeal DPSL proteins and can be observed in the primary sequence as the thioferritin motif (28). Together, these features differentiate DPSL as a new member of the ferritin superfamily.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Archaeal DPSL proteins are further distinguished by a pair of conserved cysteine residues, apparently unique to the DPSL proteins, that are juxtaposed to the bacterioferritin-like dimetal binding site. This cysteine pair and the bacterioferritin-like ferrioxidase center, all housed within a dodecameric oligomer, are hallmarks of the archaeal DPSL proteins and can be observed in the primary sequence as the thioferritin motif (28). Together, these features differentiate DPSL as a new member of the ferritin superfamily.…”
mentioning
confidence: 99%
“…For these reasons, the roles of ferritin (ftnA) and DPS in the B. fragilis oxidative stress response have been investigated in detail (33,(49)(50)(51)(52)61). However, in addition to ferritin and DPS, B.fragilis has a bacterioferritin-related gene, bfr, and a recent expression microarray study shows that expression of the bfr gene is significantly induced by exposure to air, suggesting that it might also help protect against ROS (61).Further interest in B. fragilis bfr and its gene product stems from a study suggesting that it might actually be more closely related to the archaeal DPS-like (DPSL) proteins and that the bfr gene product is a member of the newly identified miniferritin that is structurally distinct from both the larger ferritin and bacterioferritin 24-mers and dodecameric DPS (18,28). Like DPS, the archaeal DPSL proteins are expressed in response to oxidative stress, adopt the overall fold of the DPS subunit, and form dodecameric (12-mer) cage-like particles (28,40,47,67).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Intensive structural research, especially using with X-ray crystallography, has revealed a highly conserved structural fold of proteins within the Dps protein family isolated from different organisms. 12,16,17,[19][20][21][22][23][24][25] However, most of these studies mainly showed structural features common to other ferritins characterized in bacteria, including the paradigmatic ferritin (FtnA) and the hemecontaining bacterioferritin (Bfr), which are composed of at least 12 subunits folded into four-helix bundles and assembled into spherical protein shells as Dps is. 13,26) E. coli Dps has a very compact and stable structure with protrusion of the highly flexible and lysine-rich N-terminus (Fig.…”
Section: Sep22/dps As a Dna-binding Proteinmentioning
confidence: 99%